A cascade enzymatic reaction activatable gemcitabine prodrug with an AIE-based intracellular light-up apoptotic probe for in situ self-therapeutic monitoring. Issue 66 (2nd August 2017) - Han, Haijie; Teng, Wenzhuo; Chen, Tingting; Zhao, Jue; Jin, Qiao; Qin, Zhihui; Ji, Jian
Abstract : A cascade enzymatic reaction activatable gemcitabine prodrug was designed as a theranostic platform for in situ self-therapeutic monitoring of pancreatic cancer cells. Abstract : A targeted cathepsin B-activatable gemcitabine prodrug with caspase-3 specific light-up tetraphenylene (TPE) as an apoptotic probe based on aggregation-induced emission (AIE) properties was designed for in situ self-therapeutic monitoring of pancreatic cancer cells.